Evaluate the shielding effectiveness of driver's cab for metro and its influence on electromagnetic exposure safety. (October 2019) - Zhou, W Y; Lu, M
Abstract: In order to study the shielding effectiveness of metro driver cab and its impact on the safety of driver high frequency electromagnetic exposure, this paper construct the high frequency electromagnetic environment model of metro cab under the radiation of external and internal exposure sources, its shielding effect is simulated correspond, and the safety of high frequency electromagnetic exposure of metro driver is analysed. The simulation results show that the under digital trunked system antenna (external exposure source) radiation, the peak value of electric field strength inside the metro cab without aluminium alloy body is 1.7214 V/m, which 322 times higher than that of aluminium alloy cab; under the communication based train control system antenna (internal exposure source) radiation, the peak value of electric field strength inside the aluminium alloy material metro cab is 3.1625×10 −1 V/m, which 26 times higher than that of without aluminium alloy body. The compared results reveal that the shielding effect of metro cab on the external exposure source is significantly greater than the internal exposure source. Although the radiation dose absorbed by the metro driver varies by 4 to 125 times in different situation, still lower than the international occupational electromagnetic exposure limit, which indicate that the shielding effect of metro cab in the above situation will not cause health hazards to the driver.